Menurunkan Problem Reject Pinhole di Proses dengan Konsep DMAIC di PT. XYZ, Purwakarta - Hikmat Mulyana M; Andira Andira; Nurhayati Surbakti (JIE Scientific Journal on Research and Application of Industrial System, 2019)
PT XYZ is one of the flexible manufacturing industries. In terms of overcoming competition in the printing industry, PT XYZ built the Rotogravure company in 2011. The subsidiary is engaged in manufacturing Cylinder Rotogravure which supplies PT XYZ units. From a few years back since the establishment of this company, the target that should have been reached in amount of 5760 Cylinder / year. This target hasnot been achieved. This occurs because there is a problem in the production process reaching ± 49.4% and continues to appear which results in a disrupted delivery schedule, many customer complaints due to the low quality goods being shipped.The method used for this improvement process is the system or concept of Six Sigma namely DMAIC. From the DMAIC method, the tools used for the analysis process are the Pareto, Fishbone, 5W1H and Data Sheet diagrams. These tools are core tools that are focused on finding problems that often occur at PT XYZ. From the results of this improvement, a design is got to make the cleaning process aids, there were changes in parameters in the production process by reducing the current density and temperature in the Copper machine with a temperature of 30OC and current density of 20 A / dm2. The research and improvements that have been made are 94.45% with a total pinhole wastage of 1 cylinder unit.